3D hybrid finite elements for anisotropic heat conduction in a multi-material with multiple orientations of the thermal conductivity tensors. (September 2020) - Annasabi, Z.; Erchiqui, F.
Abstract: In contrast to numerical methods, which are generally poorly adapted to thermal conduction treatments in solid media containing different materials with different types of orientations of thermal conductivity tensors (Cartesian and/or cylindrical and/or spherical), the proposed new approach, 3D hybrid finite elements, is easier to implement numerically and, in particular, for the finite element method. To improve the efficiency and accuracy of the solution by FEM, we consider the implicit method using the prediction/correction strategy. The proposed approach is validated in the following cases: (i) two analytical tests for cylindrical and spherical anisotropic thermal conduction; (ii) numerical orthotropic thermal conduction in the case where the local axes of the material are not aligned with the global Cartesian axes (case of a square plate made of two different materials: one isotropic and the other orthotropic) and (iii) experimental temperature obtained on the heating of a cylindrical log. As applications, two multi-material and multi-orientation situations of the thermal conductivity tensor were considered: one related to an ignition pipe made of multiple anisotropic materials and the other to a heated chair-seat made of multiple anisotropic materials.